2021
DOI: 10.1002/smll.202005332
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Multi‐Metallic Compounds as Host Materials in Cathode for Lithium–Sulfur Batteries

Abstract: Figure 4. SEM and TEM images of NiFe 2 O 4 as host materials sulfur cathodes. a) NiFe 2 O 4 -CNTs hybrid. Reproduced with permission. [49] Copyright 2018, Elsevier. b) Fine S nanoparticles coating CNT/NiFe 2 O 4 .Reproduced with permission. [50] Copyright 2015, American Chemical Society. c) NiFe 2 O 4 hollow spheres. Reproduced with permission. [51] Copyright 2019, American Chemical Society. d) NiFe 2 O 4 nanofibers. Reproduced with permission. [52] Copyright 2018, Springer Nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 128 publications
(168 reference statements)
0
18
0
Order By: Relevance
“…Under this circumstance, spinel oxides pertaining to their flexibility in engineering cations and valence states are flexible to tune the inherent properties subjected to the diversified requirements, which have increasingly attracted extensive attention [3b] . In principle, integrating multi‐cations into one component empowers the electrocatalysts with a wide variety of features, which is exceedingly responsive to the strategies of ingeniously optimizing the electronic structure of spinel oxides for synergistically improved LiPSs redox activity [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Under this circumstance, spinel oxides pertaining to their flexibility in engineering cations and valence states are flexible to tune the inherent properties subjected to the diversified requirements, which have increasingly attracted extensive attention [3b] . In principle, integrating multi‐cations into one component empowers the electrocatalysts with a wide variety of features, which is exceedingly responsive to the strategies of ingeniously optimizing the electronic structure of spinel oxides for synergistically improved LiPSs redox activity [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Given the above limitations, the strategies about improving the performance of Li–S batteries have been an ongoing interest. Currently, the cathode, electrolyte, interlayer material, and lithium anode have been extensively investigated to limit the shuttling of polysulfides and facilitate the redox reaction of sulfur, among which the designs of a separator functional interlayer/sulfur cathode are critical in Li–S batteries. The widespread use of carbon materials can provide electron transfer and prevent the diffusion polysulfides in Li–S batteries .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, single-phase metal oxides have been identified in various crystal structures such as rock-salt-type oxides, spinel-type oxides, rutile oxide, and perovskite-based oxides. 6,7 Early research reported that common rock salt structures (e.g., NiO, MnO, CoO, and etc.) with one Wyckoff site for the cations suffer from drawbacks like insulating behavior and lattice structural dissolution in alkaline media after a prolonged period.…”
Section: Introductionmentioning
confidence: 99%
“…The development of functional materials has become an essential index to quantify the relative mechanistic insights in the energy sector. Generally, single-phase metal oxides have been identified in various crystal structures such as rock-salt-type oxides, spinel-type oxides, rutile oxide, and perovskite-based oxides. , Early research reported that common rock salt structures (e.g., NiO, MnO, CoO, and etc.) with one Wyckoff site for the cations suffer from drawbacks like insulating behavior and lattice structural dissolution in alkaline media after a prolonged period. , However, nanostructured materials of the rutile-type (e.g., TiO 2 and SnO 2 ) can lead to the formation of disordered structural characteristics during the discharge and recharging processes, thereby achieving low capacity and poor cycling stability .…”
Section: Introductionmentioning
confidence: 99%